Pengaruh Employee Engagement dan Disiplin Kerja terhadap Kinerja Karyawan pada PT Canvas Industry Indonesia - Muhamad Azka Fahmi; Suroso Suroso; Dwi Epty Hidayaty (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2026)
Employee performance is one of the important factors in supporting the achievement of company goals. Employees at PT Canvas Industry Indonesia are required to be able to meet the targets set by the company. However, in practice, there are still employees who have not shown optimal performance. Therefore, this study aims to determine and analyze the partial and simultaneous effects of Employee Engagement and Work Discipline on Employee Performance at PT Canvas Industry Indonesia. The research method used is quantitative verification. The population in this study is all employees of PT Canvas Industry Indonesia, with a sample size of 81 respondents. Data collection was conducted through questionnaires, while data analysis was performed using multiple linear regression analysis with the help of SPSS version 26. The results show that Employee Engagement has a positive and significant partial effect on Employee Performance, and Work Discipline also has a positive and significant partial effect on Employee Performance. Furthermore, simultaneous testing results show that Employee Engagement and Work Discipline have a positive and significant effect on Employee Performance. The higher the level of employee engagement with their work and company and the better the implementation of work discipline, the higher the employee performance will be. Employee Engagement and Work Discipline play an important role.